Vaccination coverage in times of COVID-19: An analysis from social epidemiology in the region of Cusco - Pereira-Victorio, Cesar Johan (2020)
Introduction: The COVID-19 pandemic could have affected vaccination coverage. Objetive: Was to estimate vaccination coverage for the years 2018-2020 and to analyze the social, economic and educational conditions related to this indicator. Material and Methods: Social epidemiological study carried out in the Cusco region with a report of vaccination coverage in the years 2018-2020 for the period January - May and with economic and educational indicators for 2019. Rates of vaccination coverage were estimated (pentavalent, polio, pneumococcal and SPR) as well as inequality variables. Gap metrics were expressed through absolute Kuznets (ika) and relative Kuznets (ikr). Results: Of 112 districts, the vaccination coverage for the 4 vaccines were on average 39%, 38% and 24% for 2018, 2019 and 2020; respectively. Accumulated vaccination coverage is similar between 2018 and 2019 according to educational and economic stratifier, but in all quintiles of 2020 there was a decrease in coverage of approximately 40%. In the years 2019 and 2020 according to schooling, the absolute and relative differences between the extreme quintiles are reversed, with higher coverage in the quintiles with less schooling compared to those with higher schooling. Conclusion: There is a decrease in accumulated vaccination coverage rates for 2020 and they differ according to quintiles of schooling and income, which is attributed to the state of sanitary emergency due to COVID-19. It is critical to monitor recovery vaccination coverage activities to prevent outbreaks of immuno-preventable diseases.